Neurofilament light chain serum levels correlate with the severity of neurotoxicity after CAR T-cell treatment - Schöberl, Florian; Tiedt, Steffen; Schmitt, Anita; Blumenberg, Viktoria; Karschnia, Philipp; Burbano, Vanessa Granja; Bücklein, Veit Leonhard; Rejeski, Kai; Schmidt, Christian; Busch, Galina; von Bergwelt-Baildon, Michael; Tonn, Jörg-Christian; et al. (Blood advances, 2022)
Antitumor therapy with CD19-targeted chimeric antigen receptor (CAR) modified T cells is highly efficient. However, treatment is often complicated by a unique profile of unpredictable neurotoxic adverse effects of varying degrees known as immune effector cell-associated neurotoxicity syndrome (ICANS). We examined 96 patients receiving CAR T cells for refractory B-cell malignancies at 2 major CAR T-cell treatment centers to determine whether serum levels of neurofilament light chain (NfL), a marker of neuroaxonal injury, correlate with the severity of ICANS. Serum NfL levels were measured before and after infusion of CAR T cells using a single-molecule enzyme-linked immunosorbent assay and correlated with the severity of ICANS. Elevated NfL serum levels before treatment were associated with more severe ICANS in both unadjusted and adjusted analyses. Multivariable statistical models revealed a significant increase in NfL levels after CAR T-cell infusion, which correlated with the severity of ICANS. Preexisting neuroaxonal injury. which was characterized by higher NfL levels before CAR T-cell treatment, correlated with the severity of subsequent ICANS. Thus, serum NfL level might serve as a predictive biomarker for assessing the severity of ICANS and for improving patient monitoring after CAR T-cell transfusion. However, these preliminary results should be validated in a larger prospective cohort of patients.
Gesehen am 24.08.2022